Morphological Characterization of Rust Resistant and Susceptible Genotypes of Groundnut (Arachis Hypogaea L.) (Journal of Plant Disease Sciences, 2019)
Twelve groundnut (Arachis hypogaea) genotypes viz. ICG 13165, ICG 13160 (wild resistant) RHRG-6083, GPBD-4, KDG-128, ICG-11426, ICG-12672, ICGV-86590, ICGV-94118, ICGV-96283 (cultivated resistant) and SB- XI and JL- 24 (highly susceptible), were evaluated for resistance to rust (Puccinia arachidis) under artificial epiphytotic conditions. Morphological characters viz., stomatal frequency and size, thickness of epidermis cum cuticle, number of trichomes were estimated among the cultivars having different degree of resistance. The stomatal frequency and size was less in resistant cultivar and more in susceptible cultivar, SB-XI and JL-24. Average thickness of epidermis-cum cuticle was significantly higher on the adaxial and abaxial leaf surface in the resistant genotypes and lower on adaxial and abaxial leaf surface in the susceptible genotypes. The resistant genotypes had significantly higher frequency of trichomes than those of susceptible genotypes. These differences were considered as partial contributing morpho- anatomical features of defense system of groundnut to rust.
Keywords: Groundnut; rust; Puccinia arachidis; Arachis hypogaea; artificial epiphytotic